Sibling’s Support and Menstrual Hygiene among Early Adolescent Girls in Serang District, Banten Province, Indonesia - Wahyuni, Tri; Ritanti, Ritanti (Media Keperawatan Indonesia, 2024)
Menstrual hygiene is critical for preventing adverse health outcomes, yet many adolescent girls in low and middle-income countries, including Indonesia, face barriers such as inadequate knowledge, limited access to sanitary materials, and cultural taboos, increasing their risk of reproductive tract infections. This study aims to determine the prevalence of bad menstrual hygiene and its association with sibling support and information exposure among early adolescent girls in Banten Province, Indonesia. This cross-sectional study involved 367 early adolescent girls aged 12–15 years who had experienced menarche, selected using a simple random sampling technique. Data were analyzed using multivariable logistic regression. The prevalence of bad menstrual hygiene was 53.68% (197/367). Sibling support (adjusted OR = 0.92, 95% CI: 0.85–0.99, p = 0.045) was a protective factor, while information exposure (adjusted OR = 2.79, 95% CI: 1.81–4.30, p < 0.001) significantly increased the risk of bad menstrual hygiene. A high prevalence of bad menstrual hygiene was observed among early adolescent girls in Banten Province. Strengthening sibling support and improving information exposure could be effective strategies to enhance menstrual hygiene management.